LIMITATIONS ON NON-PHYSICAL SEXUAL ACTS IN THE LAW 12 OF 2022 CONCERNING CRIMINAL ACTIONS OF SEXUAL VIOLENCE AS AN ANALYSIS - Aliza Yohana S; Md. Shodiq; Ramlani Lina Sinaulan; Aturkian Laia; Nur Afiah; Abdul Rahmat (European Journal of Humanities and Educational Advancements, 2024)
Cases of sexual violence are like an iceberg phenomenon, where the visible cases are only a phenomenon that occurs on the surface . Research result This is In non-physical sexual violence as regulated in Article 4 of the Sexual Violence Crime Law, there is a need for an explanation regarding what non-physical sexual violence is and protection. law towards victims of violence sexual arranged in laws , among others Constitution about Act Criminal Violence Sexual , Law about Protection child , Act about Information and Technology Electronics , and the Criminal Code . Formulation mass in study This is How characteristics follow criminal violence non- physical sexual ? And how protection law towards victims of violence non- physical sexual ? Research methods This use normative law